2021
DOI: 10.1002/aqc.3574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sea‐level rise and storm‐enhanced flooding on Pacific harbour seal habitat: A comparison of haul‐out changes at the Russian and Eel river estuaries

Abstract: 1. Patterns and changes in the distribution of coastal marine mammals can serve as indicators of environmental change that fill critical information gaps in coastal and marine environments. Coastal habitats are particularly vulnerable to the effects of near-term sea-level rise.2. In California, Pacific harbour seals (Phoca vitulina richardii) are a natural indicator species of coastal change because of their reliance on terrestrial habitats, abundance, distribution, and site fidelity. Pacific harbour seals are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Regional data on survival rates of pups in southwest England would allow us to better understand trends in the abundance of seals in this region. While it would be of interest to understand how inclement weather drives the timing of stranding events (Truchon et al, 2013;Vishnyakova and Gol'din, 2014;Prado et al, 2016;Sepúlveda et al, 2020;Backe et al, 2021), upon initial exploration of these factors (Figures S4-S6), we found the complicated coastline with diverse aspects, presence of islands and relatively small sample sizes of each life stage per month in any given year, precluded a correlative approach, at this stage.…”
Section: Seasonalitymentioning
confidence: 99%
“…Regional data on survival rates of pups in southwest England would allow us to better understand trends in the abundance of seals in this region. While it would be of interest to understand how inclement weather drives the timing of stranding events (Truchon et al, 2013;Vishnyakova and Gol'din, 2014;Prado et al, 2016;Sepúlveda et al, 2020;Backe et al, 2021), upon initial exploration of these factors (Figures S4-S6), we found the complicated coastline with diverse aspects, presence of islands and relatively small sample sizes of each life stage per month in any given year, precluded a correlative approach, at this stage.…”
Section: Seasonalitymentioning
confidence: 99%
“…Both species select terrestrial sites with minimal disturbances, limited slopes, and protection from high surf, with a preference for sandy beaches or sandbanks , Lester & Costa, 2006, Rick et al, 2011, Thompson et al, 1997. Based on coordinates from the PRNS Seal Count database , and confirmed through published research (Allen et al, 2011, Allen et al, 1989, Backe et al, 2021., Codde et al, 2011, Codde, 2020, Funayama et al, 2013, we obtained a total of 26 seal haul-out locations either currently used by each species as haulouts or considered as a potential a site due to SLR. The 26 coordinates were converted into point locations, 10 for northern elephant seals and 16 for Pacific harbor seals, using a GIS (Figure 1 and Table 1).…”
Section: Study Areamentioning
confidence: 90%